Quantitative studies on the role of Ureaplasma urealyticum in non-gonococcal urethritis and chronic prostatitis. - Brunner, H. (Yale Journal of Biology and Medicine, 1983)
Quantitative determinations of U. urealyticum and M. hominis have been performed in 164 men with non-gonococcal urethritis (NGU) and 597 patients with chronic prostatitis. Evidence is provided that U. urealyticum plays an etiologic role in 29.3 percent of patients with non-gonococcal urethritis. Mixed infections of C. trachomatis and U. urealyticum, in high numbers, do occur in 11 percent of NGU cases. A constellation suggesting ureaplasma-associated disease could be observed in 13.7 to 15.2 percent of 597 patients with chronic prostatitis. M. hominis does not appear to be a causative agent of NGU or chronic prostatitis.